FGFR2 loss sensitizes MYCN‐amplified neuroblastoma CHP134 cells to CHK1 inhibitor–induced apoptosis. Issue 2 (30th November 2021) - Ando, Kiyohiro; Ohira, Miki; Takada, Ichiro; Cázares‐Ordoñez, Verna; Suenaga, Yusuke; Nagase, Hiroki; Kobayashi, Shinichi; Koshinaga, Tsugumichi; Kamijo, Takehiko; Makishima, Makoto; Wada, Satoshi
Abstract: Checkpoint kinase 1 (CHK1) plays a key role in genome surveillance and integrity throughout the cell cycle. Selective inhibitors of CHK1 (CHK1i) are undergoing clinical evaluation for various human malignancies, including neuroblastoma. In this study, one CHK1i‐sensitive neuroblastoma cell line, CHP134, was investigated, which characteristically carries MYCN amplification and a chromosome deletion within the 10q region. Among several cancer‐related genes in the chromosome 10q region, mRNA expression of fibroblast growth factor receptor 2 ( FGFR2 ) was altered in CHP134 cells and associated with an unfavorable prognosis of patients with neuroblastoma. Induced expression of FGFR2 in CHP134 cells reactivated downstream MEK/ERK signaling and resulted in cells resistant to CHK1i‐mediated cell growth inhibition. Consistently, the MEK1/2 inhibitor, trametinib, potentiated CHK1 inhibitor–mediated cell death in these cells. These results suggested that FGFR2 loss might be prone to highly effective CHK1i treatment. In conclusion, extreme cellular dependency of ERK activation may imply a possible application for the MEK1/2 inhibitor, either as a single inhibitor or in combination with CHK1i in MYCN ‐amplified neuroblastomas. Abstract : FGFR2 loss indicated cells that were prone to highly effective CHK1 inhibitor treatment, whereas increased FGFR2 expression implied a possible application for a targeting therapy for MEK/ERK signaling, either as a single inhibitor or in combination with CHK1 inhibitor in neuroblastomas.